Opposite modulation of brain stimulation reward by NMDA and AMPA receptors in the ventral tegmental area - Ducrot, Charles; Fortier, Emmanuel; Bouchard, Claude; Rompre, Pierre Paul (Frontiers in Systems Neuroscience, 2013)
Previous studies have shown that blockade of ventral midbrain (VM) glutamate N-Methyl-D-Aspartate (NMDA) receptors induces reward, stimulates forward locomotion and enhances brain stimulation reward. Glutamate induces two types of excitatory response on VM neurons, a fast and short lasting depolarisation mediated by a-amino-3-hydroxy-5-methyl-4-isoxazole propionate (AMPA) receptors and a longer lasting depolarization mediated by NMDA receptors. A role for the two glutamate receptors in modulation of VM neuronal activity is evidenced by the functional change in AMPA and NMDA synaptic responses that result from repeated exposure to reward. Since both receptors contribute to the action of glutamate on VM neuronal activity, we studied the effects of VM AMPA and NMDA receptor blockade on reward induced by electrical brain stimulation. Experiments were performed on rats trained to self-administer electrical pulses in the medial posterior mesencephalon. Reward thresholds were measured with the curve-shift paradigm before and for two hours after bilateral VM microinjections of the AMPA antagonist, NBQX (2,3,-Dioxo-6-nitro-1,2,3,4-tetrahydrobenzo(f)quinoxaline-7-sulfonamide, 0, 80, and 800 pmol/0.5ul/side) and of a single dose (0.825 nmol/0.5ul/side) of the NMDA antagonist, PPPA (2R,4S)-4-(3-Phosphonopropyl)-2-piperidinecarboxylic acid). NBQX produced a dose-dependent increase in reward threshold with no significant change in maximum rate of responding. Whereas PPPA injected at the same VM sites produced a significant time dependent decrease in reward threshold and increase in maximum rate of responding. We found a negative correlation between the magnitude of the attenuation effect of NBQX and the enhancement effect of PPPA; moreover, NBQX and PPPA were most effective when injected respectively into the anterior and posterior VM. These results suggest that glutamate acts on different receptor sub-types, most likely located on different VM neurons, to modulate reward.